Need Analisys: Pengembangan Media Pembelajaran Alphabet Animals E-book berbasis Augmented Reality untuk Meningkatkan Kemampuan Keaksaraan Anak Usia 5-6 Tahun - Putri, Vannessa Ajeng Trisna; Hasni, Uswatul; Amanda, Rizki Surya; Sofyan, Hendra (Jurnal Ilmiah POTENSIA, 2025)
Literacy is a basic skill that young children need to have as preparation for reading and writing. Literacy abilities can be developed through learning media that is appropriate to the child's developmental stage. This research aims to identify the need for developing augmented reality-based Alphabet Animals E-book learning media to improve literacy in children aged 5-6. This research uses a descriptive qualitative approach. Identification of needs is based on three aspects, namely learning media, learning strategies, and analysis of children's literacy development abilities. The subjects of this research consisted of 5 teachers and principals of kindergarten schools in Jambi Luar Kota District, Jambi Province. The data collection techniques used were interviews and documentation. Data analysis was carried out using the Miles and Huberman technique, which includes data collection, data reduction, data display, and conclusion/verification stages. The research results show that children aged 5-6 years need learning media, such as alphabet animals e-books based on augmented reality, to improve their literacy skills.